Filtros físicos en el tratamiento de las aguas residuales domésticas para su reutilización en regadío en la I.E N°00813, Ochamé – Moyobamba - Arista Reategui, Willy Jhon (2015)
The research work was carried out in l. E N°. 00813, located in Ochame town, Moyobamba district, Moyobamba province, San Martin department, taking as its objective to determine the effect the physical filters in the treatment of domestic wastewater for reuse in irrigation, considering the physical, chemical and bacteriological parameters of the residual water (pH, 0805, OQO, SST and Total coliforms), the same who were compared with the Environmental Quality Standards (ECA) laid down in the national standards. The literature review led to assume that if we use physical filters in the treatment of domestic wastewater, then we would get useable water in irrigation, which formed the research hypotheses. In the operative part, research was conducted under an experimental design with pre- and post-test, and during the period of operation of the filters were six physical samples of wastewater; in which each sample was 500 mi; taking a total of 3 liters; which formed the sample. In terms of results, using three physical chemical analysis and microbiological parameters, were determined from SST, pH, Total Coliforms, 0805 y OQO to the domestic residual water, the same that are below the established values in ECA for irrigation, making it clear in this way that the water (effluent) is fit to be reused in irrigation; which has been proved to perform the respective hypothesis test, using the student-t distribution with 95% confidence. With regard to the removal of pollutants, the results obtained during the process of investigation showed that the filters as physical units for domestic wastewater treatment achieved have positive effects, in such a way that the removal reached for SST is 82.86 %, for total coliforms it is 77.13 %, for the 080 there was reached a removal of 96.94 % and for the OQO it was reached to remove 92.95%. Finally, it was demonstrated that the treated water with physical filters and reused in irrigation (plants of high stem) provides the greatest amount of nutrients when compared with the control soil. Key words: physical filters, domestic wastewater.